1974
DOI: 10.1039/c3974000996a
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray structure of a novel bidentate polypyrazolylborate complex: carbonyl[hydrodotris(pyrazol-1-yl)borato]methylplatinum

Abstract: The crystal structure of a bidentate hydridotris(pyrazo1-l-y1)borate complex with platinum(I1) is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The air- and moisture-stable dihydridomethyl complex TpPtMeH 2 has been obtained from reaction of TpPt(CO)Me with water . TpPt(CO)Me exists as rapidly interconverting pentacoordinated κ 3 and tetracoordinated square-planar κ 2 forms in solution (Scheme ); in the solid state the square-planar κ 2 form is assumed. , Protonation of TpPt(CO)Me results in cleavage of a Pt−N bond to give the κ 2 structure that contains the N-protonated Tp ligand (HTp). It is not known whether ligand protonation occurs before or after “slippage” from a κ 3 to κ 2 coordination mode.…”
Section: 21 Tpptmeh2 and Tp‘ptmeh2mentioning
confidence: 99%
“…The air- and moisture-stable dihydridomethyl complex TpPtMeH 2 has been obtained from reaction of TpPt(CO)Me with water . TpPt(CO)Me exists as rapidly interconverting pentacoordinated κ 3 and tetracoordinated square-planar κ 2 forms in solution (Scheme ); in the solid state the square-planar κ 2 form is assumed. , Protonation of TpPt(CO)Me results in cleavage of a Pt−N bond to give the κ 2 structure that contains the N-protonated Tp ligand (HTp). It is not known whether ligand protonation occurs before or after “slippage” from a κ 3 to κ 2 coordination mode.…”
Section: 21 Tpptmeh2 and Tp‘ptmeh2mentioning
confidence: 99%
“…Variable-temperature NMR experiments have indicated that 2 in CDCl 3 solution is fluxional at room temperature but adopts a trigonal-bipyramidal geometry, 2a , at low temperatures. In the solid state, however, the molecule takes a square-planar geometry, 2b , with the Tp group becoming a bidentate ligand .…”
mentioning
confidence: 99%
“…An essentially square planar environment about each Pt(II) atom in the series PtN 2 C 2 is created in two derivatives (Lopez et al 1992 ) solely by unidentate ligands, and in 17 derivatives (Rush and Oliver 1974, Oliver and Rice 1976, Klinger et al 1982, Bruno et al 1990, Deacon et al 1991, Klein et al 1992, Klein et al 1995, Ng et al 1996, Acher and Catalano 1997, Wick and Golberg 1997, Johansson et al 1998, Haskel and Keinan 1999, Steinborn et al 1999 bidentate − N,N ′ (mostly 2,2 ′ -bipyridine) and its derivatives. In another two Minchin 1983 , Carty et al 1992 ), a bidentate − N,C donor ligand with a unidentate N and C donor ligand creates a PtN 2 C 2 environment.…”
Section: Ptn 2 C 2 Ptc 2 Cl 2 and Ptc 2 S 2 Chromophoresmentioning
confidence: 99%